Geotechnical Monitoring Of High-Level Nuclear Waste Repository Performance - Christopher M. St. John; Michael P. Hardy (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
The paper discusses an approach to geotechnical monitoring of a geological repository constructed for the purpose of isolation of high-level nuclear waste, and describes the conceptual framework for development of an integrated monitoring scheme that is initiated during the earliest phases of site investigation and continues through facility decommissioning. The approach that is proposed recognizes the need to provide specific data to support the licensing process for the repository while avoiding adverse impact upon the system performance. Further, it recognizes present and inherent limitations in both the instrumentation and techniques that night be used within a monitoring scheme.